Association between Sympathetic Nervous System Activation, Obesity and Insulin Resistance - A. I. Kochetkov; O. D. Ostroumova; A. V. Starodubova; Т. М. Оstroumova; D. A. Bondarenko (Рациональная фармакотерапия в кардиологии)
The review discusses the problem of overweight, obesity and metabolic syndrome and their activating effect on the sympathetic nervous system and the increase in blood pressure. Current epidemiological data on the prevalence of obesity and metabolic syndrome and trends in their occurrence in recent decades are presented, indicating the high significance of these disorders in modern health care and their important role in development of the overall disease burden. In accordance with the clinical guidelines, types of obesity are described with a special focus on its abdominal type, as a factor that increases cardiovascular risk. The mechanisms of sympathetic overactivity in obesity, including insulin resistance, hyperleptinemia, the effect of nonesterified fatty acids, obstructive sleep apnea and baroreflex impairment are considered in detail. In the second part of the paper experimental and clinical findings are presented indicating worsening of the hypertension mediated target-organ damage in the presence of concomitant obesity that emphases on the crucial role of amplified adrenergic stimuli in the formation of these disorders. The promoting effect of obesity and concomitant sympathetic nervous system overactivation on the development of left ventricular hypertrophy, endothelial dysfunction and vascular damage, renal dysfunction and cognitive decline are considered. Finally, body of evidence of high antihypertensive efficacy as well as prominent target organ protective features of the highly selective β1-blocker bisoprpolol are presented especially when it prescribed in patients with arterial hypertension and concomitant obesity and metabolic syndrome.